Hubungan Adaptasi Fisiologis dan Adaptasi Psikologis dengan Diet Diabetes Melitus pada Pasien Diabetes Melitus Tipe 2 - Muhamad Nurmansyah; Rina Margaretha Kundre (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Diabetes Mellitus (DM) is a group of metabolic diseases with characteristic of hyperglycemia that occurs due to insulin secretion disorders, insulin performance, or both. According to the International Diabetes Federation (IDF) in 2015, prevalence of dibetes mellitus in the world in adults increased according to data in 2014 where 1 in 11 adults with diabetes. Increased cases of diabetes mellitus also followed by the increase of accompanying complications itself. Complications of diabetes mellitus caused variety of problems not only physical problems, but also psychological problems. The purpose of this study was to investigate the relationship between physiological and psychological adaptation to dietary compliance in type 2 diabetics. This study was an observational descriptive study with cross sectional approach. This study involved 100 people type 2 diabetics in Sario health center as a samples. Statistical test results with a level of meaning p